Efficacy and cost efficiency of weed management using generic herbicide, adjuvant and drone application in oil palm plantations - Che Ruzlan, Kamalul Adham (2023)
A strategy that balances effective weed control and costs in oil palm plantations is crucial amidst rising herbicide expenses and soil erosion concerns. Herbicides offer cost-effectiveness and efficacy method over manual weeding. However, rising herbicide costs, exemplified by the 39% increase in Felda Global Ventures (FGV) in 2021, demand immediate attention. Therefore, this study aims to optimize herbicide efficacy and cost efficiency by addressing weed management challenges, comparing premium and generic herbicides, evaluating the additive effect of WEED Solut-ioN®, and assessing drone-assisted blanket spraying and purification of legume cover crops during replanting. The research utilized questionnaires and field experiments. The survey covered FGV plantations across Malaysia, with experiment trials conducted at Tun Razak Agriculture Centre, Jengka, Pahang and Felda Global Venture Plantation Malaysia (FGVPM) Mengkarak 2, Bera, Pahang. In study 1, two surveys were conducted in oil palm plantations across Malaysia: one on weed management practices and issues, and another on the performance of generic herbicides. Chemical (herbicide) approach was the predominant weed control approach employed, followed by biological control, mechanical control, integrated weed management, and cultural practices. Common issues faced by planters included labor, herbicide resistance, high cost, knowledge, practical issues, low productivity, and herbicide efficacy. The survey on generic herbicide performance revealed that most planters favored generic products due to cost. However, they noted issues like inconsistent weed control and less effectiveness. Study 2 found that generic herbicides performed similarly to premium herbicides. Across all assessments in both immature and mature oil palm settings, generic herbicides achieved 93% to 97% of weed control efficiencies compared to the slightly superior control by premium herbicides (98% to 100%). Cost projections indicated substantial cost savings associated with the use of generic herbicides, with a 47% cost reduction in immature stages and around 12% in palm circles. Savings for controlling broadleaf and woody weeds approached 14% in both scenarios. Given that all generic herbicides assessed in this study achieved over 90% weed control efficiency, their adoption presents a cost-effective alternative to premium herbicides. Study 3 revealed the effectiveness of WS in reducing the amount of herbicide required to control weeds, resulting in a 50% of reduction in herbicide dosage for circle weeding in immature oil palms and 70% for inter-row weeding and selective weed control of C. hirta in mature oil palms. Phytotoxicity evaluations on eight-month-old oil palm trees indicated WS as a non-phytotoxic reductant, posing no harm to oil palm growth or yield, with minimal impact on Elaedobius kameranicus (weevils) even at a higher concentration (at 2 L/ha). Economic analyses demonstrated the substantial cost-saving potential of WS, resulting in up to 25% of reduction for immature palms and up to 14% for mature palms. Overall, WS can save FGV up to RM10,776,617 per year on weeding costs. WEED Solut-ioN® emerges as a highly effective and sustainable solution for weed control in oil palm plantations. Study 4 showed that 0.25 MPa pressure was more effective than 0.15 MPa as it provided broader coverage and more droplets. In replanting areas, both UAV and mistblower applications resulted in 100% weed eradication, demonstrating equal effectiveness. In pre-planting zones, the initial advantage of conventional knapsack sprayers (CKS) diminished over time, highlighting the UAV spray's enhanced efficacy. UAV spraying becomes cost-effective for areas over 3,000 hectares, with potential savings ranging from 4% to 28%. Furthermore, UAV spraying reduced working hours by 37%, water usage by 91%, and human expenses by 81% compared to conventional methods, highlighting its efficiency and cost saving benefits for large-scale weed control in oil palm plantations. Overall, this research offers insights into optimizing weed control in oil palm plantations, emphasizing cost efficiency and sustainability through strategic herbicide selection, additive solutions like WEED Solut-ioN®, and innovative techniques such as UAV spraying.